2018
DOI: 10.1186/s40608-018-0207-3
|View full text |Cite
|
Sign up to set email alerts
|

Separating “good” from “bad” faecal dysbiosis – evidence from two cross-sectional studies

Abstract: BackgroundFaecal dysbiosis associated with the use of metformin has been conceived as a favourable (“good”) dysbiosis and that with intake of non-nutritive sweeteners (NNS) as unfavourable (“bad”). The study aimed to construct an alternative dysbiosis index (ADI) for the separation of the dysbioses into “good” and “bad”, and to validate the ADI.MethodsSubjects with morbid obesity were included. Use of NNS and drugs were noted, IBS was classified according to the Rome III criteria and the severity measured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 35 publications
1
14
0
1
Order By: Relevance
“…The method used for the analyses of the microbiota composition did not allow precise characterization of the microbiota and the changes of the microbiota since the method measured only 39 bacteria at different taxonomic levels. The same changes were in a previous study based on the same material judged as unfavorable ("bad" dysbiosis) [34]. In contrast to the review by Wagner el al., this study showed a significant increase in the relative amount of the phylum Firmicutes and a non-significant reduction in Bacteroidetes [5].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The method used for the analyses of the microbiota composition did not allow precise characterization of the microbiota and the changes of the microbiota since the method measured only 39 bacteria at different taxonomic levels. The same changes were in a previous study based on the same material judged as unfavorable ("bad" dysbiosis) [34]. In contrast to the review by Wagner el al., this study showed a significant increase in the relative amount of the phylum Firmicutes and a non-significant reduction in Bacteroidetes [5].…”
Section: Discussionsupporting
confidence: 65%
“…NNS, which was used in high amounts by a substantial proportion of the participants, were not associated with changes in SCFA. An association was anticipated since NNS induce marked changes in the gut microbiome [31][32][33][34]. Separate analyses during the conservative weight-loss period with primarily dietary restrictions could perhaps have shown more explicit associations between changes in the diet and changes in the SCFA.…”
Section: Discussionmentioning
confidence: 99%
“…NNS have been associated with metabolic disorders in observational studies [27]. That NNS may impact the intestinal permeability through alterations in the gut microbiota is a hypothesis that could be explored further [28].…”
Section: Fig 1 Inclusion Of Participantsmentioning
confidence: 99%
“…The data used were a subset of data from in a study in subjects with morbid obesity, the MO-BiPS study (Morbid Obesity-Bio-Psycho-Social disorders) [10][11][12][13].…”
Section: Methodsmentioning
confidence: 99%